Accumulation of dry mass and macronutrients by sourgrass plants - Carvalho, L.b.; Bianco, M.s. [UNESP]; Bianco, S. [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 2013)
The experiment was carried out aiming to analyze the dry mass production and distribution and the content and accumulation of macronutrients in sourgrass (Digitaria insularis) plants cultivated under mineral nutrition standard conditions. Plants grew in 7-liter pots filled with sand substrate and daily irrigated with nutrient solution, being maintained under greenhouse conditions. Treatments consisted of times of evaluation (21, 35, 49, 63, 77, 91, 105, 119, and 133 days after emergence - DAE) and were arranged in a completely randomized design with four replicates. Sourgrass showed small accumulation of dry mass (0.3 g per plant) and macronutrients (3.7 mg of N per plant, 0.4 mg of P per plant, 5.6 mg of K per plant, 0.9 mg of Ca per plant, 0.7 mg of Mg per plant, and 0.3 mg of S per plant) at vegetative growth stage (< 49 DAE). Those accumulations increased mainly after 77 DAE, reaching the maximum theoretical value at 143, 135, 141, 129, 125, 120, and 128 DAE, for dry mass (12.4 g per plant), N (163.2 mg per plant), P (27.1 mg per plant), K (260.5 mg per plant), Ca (47.6 mg per plant), Mg (30.9 mg per plant), and S (13.7 mg per plant), respectively. K and N were found with higher rates and, as a consequence, they were required and accumulated in greater amounts in plant tissues of sourgrass.

O experimento foi conduzido com o objetivo de analisar a produção e a distribuição de massa seca e os teores e os acúmulos dos macronutrientes em plantas de capim-amargoso (Digitaria insularis) cultivadas em condições padronizadas de nutrição mineral. As plantas foram cultivadas em vasos de sete litros, com substrato de areia, irrigadas diariamente com solução nutritiva e mantidas em casa de vegetação. Os tratamentos corresponderam às épocas de avaliação (21, 35, 49, 63, 77, 91, 105, 119 e 133 dias após a emergência - DAE) e foram arranjados em delineamento experimental inteiramente casualizado com quatro repetições. Capim-amargoso apresentou pequeno acúmulo de massa seca (0,3 g por planta) e de macronutrientes (3,7 mg de N por planta; 0,4 mg de P por planta; 5,6 mg de K por planta; 0,9 mg de Ca por planta; 0,7 mg de Mg por planta; e 0,3 mg de S por planta) na fase vegetativa (< 49 DAE). Esses acúmulos se intensificaram, principalmente, após 77 DAE, atingindo o máximo valor teórico aos 143, 135, 141, 129, 125, 120 e 128 DAE, para massa seca (12,4 g por planta), N (163,2 mg por planta), P (27,1 mg por planta), K (260,5 mg por planta), Ca (47,6 mg por planta), Mg (30,9 mg por planta) e S (13,7 mg por planta), respectivamente. K e N foram os macronutrientes com maiores teores encontrados e, consequentemente, mais requeridos e acumulados em maiores quantidades nos tecidos vegetais das plantas de capim-amargoso.
Acúmulo de massa seca e macronutrientes em plantas de capim-amargoso
Keywords: Digitaria insularis; crescimento de plantas; nutrição mineral; Digitaria insularis; plant growth; mineral nutrition